The Influence of Financial Literacy and Shopping Habits on The Financial Management of Economic Education Students - Jerry Rommy Herter Wuisang; Agnes Rooroh; William Christian (AIBPM Publisher, 2023)
This study aims to evaluate the degree of financial literacy and spending habits of economics students at Manado State University. The statistical analysis in this research was facilitated using the SPSS 25 software. During the 2019-2020 school years, 214 students enrolled in the economics education department at Manado State University served as the sample for this study. This study included data from 68 participants. Sixty-eight participants answered the survey using the Slovin method, which has a 10% margin of error. The number of participants was chosen at random. Questionnaires were distributed and analyzed using statistical tests including the t-test and the f-test. A partial impact of X1 on Y with a significance level of 0.486 is statistically significant. The t-value arrived at through computation was 0.700, which is lower than the t-table value of 1.999. The X2 partial impact on Y has a sig value of 0.000, less than 0.05. The calculated value of t, 3,702, is larger than the value of t in the table, which is 1,999. With a sig value of 0.002, the combined effect of X1 and X2 on Y is statistically insignificant (p 0.05).